Evaluation on hand, foot and mouth disease surveillance system in children 0-9 years old in community hospitals, Ang Thong Province, April – September in 2016 and 2017 - Intarapradit, Phakphum; Khamtanot, Suwapat (Journal of Medical and Public Health Region 4, 2020)
Hand, foot, and mouth disease (HFMD) can be easily transmitted and can make a life-threatening condition. Incidence in Thailand tends to increase every year. In 2017, Ang Thong Province reported the morbidity rate of 139.23 per 100,000 population which was 2 times as high as the previous 5-year (2012-2016) median. This study aimed to describe HFMD surveillance system, its quantitative and qualitative attributes, and provide recommendations for improvement of the surveillance. A cross-sectional study was conducted in 6 community hospitals in Ang Thong Province by reviewing medical records of HFMD cases who received treatment in these hospital during April – September in 2016 and 2017. The study compared HFMD data between those in the hospital registration and in the surveillance system (R506) to determine quantitative attributes of the surveillance. Those personnel involved in HFMD surveillance system were interviewed to determine qualitative attributes of the surveillance. The results found that the sensitivity of the surveillance was 76.26% and the positive predictive value was 58.19%. Hospitals with high incidence reports of HFMD had higher sensitivity than those hospitals with low incidence reports. However, the positive predictive value in the hospitals with high incidence reports was similar to that in the hospitals with low incidence reports. Timeliness, data quality and representativeness of the surveillance were good. Health personnel were more aware of the HFMD situation following an outbreak and stated that the surveillance system was simple, flexible, acceptable and useful. However, a few personnel reported some delay of reporting when the person in charge of surveillance was absent. A low positive predictive value might be due to early diagnosis without sufficient clinical manifestations and incomplete medical records.